IT : DIGITAL FORENSIC - . Pratomo Djati Nigroho; MUhammad Nuh Al-Azhar (Universitas Insan Pembangunan Indonesia, 2017)
Pratomo Djati Nugroho, S.Pi., M.Kom., CHFIDosen STMIK Insan Pembangunan, Bitung. Tangerang.Data Members Registration of Indonesia Forensic Digital Association (AFDI)Komisaris Besar Polisi Muhammad Nuh Al-Azhar, M.Sc., CHFI., CEI., ECIHChairman of Indonesia Forensic Digital Association (AFDI)Digital Forensic Analysis Team (DFAT) PUSLABFOR MABES POLRIABSTRAKThe increasing of information technology in fact followed by issues around cybercrime and computer security.Nowadays, many cases of law has opened our mind and shows us the critical of digital forensic as the method inproofing crimes beside the law and role of regulation that happening. As more criminals utilize technology toachieve their goals and avoid apprehension, there is a developing need for individuals who can analyze and utilizeevidence stored on and transmitted using computers. By applying science methods in investigating digital evidence,made digital forensic as the answer of law standing effort in digital era.Kata kunci : Digital Forensic, Evidence, Cybercrime.